Analisis Sosial Ekonomi Masyarakat Di Zona Rehabilitasi Taman Nasional Meru Betiri, Jember, Jawa Timur (Kasus Di Desa Andongrejo, Wonoasri, Curahnongko Dan Sanenrejo) - Subaktini, Dewi (Universitas Muhammadiyah Surakarta, 2006)
National Park of Meru Betiri (TNMB) is one of National Park which exist in the region tip East Java Part of South arch residing in region tip East Java Part of South arch. This National Park has various function in protecting system of the life of flora and fauna with the ecosystems. The existence of National Park has a big advantagerus for the communities who live around the area. Along with change of period to governance in the new order becomes a reform governance makes the TN-MB ruined as the effect of foray. Hall Management of DAS Sampean-Madura (2002) reports that National Park of Meru Betiri which its width 58.000 Ha, for about 4.023 Ha have destroyed without vegetation or it becomes farm of season crop. With that condition, so the area is specified as Rehabilitation zone The research is conducted with the method of survey then clarified with the method of Participatory Rural Appraisal (PRA). Analyses data used by the descriptive analysis qualitative. The result of the research can be known that there is a high resistence or threat to the society who live around the TN MB which specified with the job where mostly as a farmer ( 35,86 %) and hard farmer (38,74 %) while the most agraris 16,6 person / Ha. Mineâs land for about 0,219 Ha / KK and productive age 63,8 %. So, it can be conclude that the rehabilitation of TN MB for this time is more concentrate to the zone area of rehabilitation and the edvantage of avoiding the farm to the jungle zone and conten zone. It is also necessary that the factor of social economic not only used to formulate the zonasi but it also used as a basis for a reconstruction of Merubetiri National Park.